Anuran Amphibians from RPPN Campo Escoteiro Geraldo Hugo Nunes, Guapimirim Municipality, Rio de Janeiro, Southeastern Brazil - Silva-Soares, Thiago; Hepp, Fabio; Costa, Paulo Nogueira; Luna-Dias, Cyro de; Gomes, Márcia dos Reis; Silva, Ana Maria Paulino Telles de Carvalho e; Silva, Sergio Potsch de Carvalho e (Biota Neotropica, 2010)
We studied the anuran amphibians from RPPN Campo Escoteiro Geraldo Hugo Nunes. The region is located in the Municipality of Guapimirim, State of Rio de Janeiro, in Southeastern Brazil and represents a lowland Atlantic Rainforest remaining, which has 45.2 ha. The hydromorphic soil is conducive to the occurrence of permanent and temporary wetlands. For the study, we carried out field expeditions since the 1980's, being the collected specimens housed at the zoological collection of the Instituto de Biologia, Universidade Federal do Rio de Janeiro. A total of 40 amphibian species of the order Anura have been found at the study site. The species are distributed in 10 families: Hylidae (N = 23), Bufonidae (4), Leptodactylidae (4), Cycloramphidae (2), Microhylidae (2), and Brachycephalidae, Craugastoridae, Hemiphractidae, Leiuperidae and Strabomantidae with one species each. Data on local reproductive environments of the recorded species are provided.